XPS profile analysis on CdS thin film modified with Ag by an ion exchange - Ristova, M; Ristov, M (Applied surface science, 2001)
Thin CdS films were produced by the method of chemical bath deposition. The composition of the film surface was modified with Ag by their immersion in 0.025 M thiosulfate Ag + complex solution for 60 s. After 3–4 months, films underwent XPS analysis. The peaks on the Auger electron spectrum were identified to originate from Cd, Ag, S, O and C electrons. Depth profile electron spectra were taken for 15 different depths of the film profile. AgMNN and CdMNN, Cd3d, S2p, Ag3d and O1s peaks were subject to detailed qualitative and quantitative analysis. Results of the quantitative profile analysis showed that the Ag +-ions from the ion exchange solution, introduced into the CdS thin film by this method, displace the Cd +2 ions during the substitution diffusion by a kick-out mechanism, forming Ag 2S. The distribution of Ag 2S in the film profile could be fitted to a exponential curve. The overall Ag 2S concentration in the thin CdS film was calculated from the integral of the normalized fitted curve over the entire film thickness. The data from the film profile was related to the optical and electrical properties of the Ag modified CdS films, which were the subject of study in our previous research.